2013
DOI: 10.1186/1465-9921-14-101
|View full text |Cite
|
Sign up to set email alerts
|

Antiflammin-1 attenuates bleomycin-induced pulmonary fibrosis in mice

Abstract: BackgroundAntiflammin-1 (AF-1), a derivative of uteroglobin (UG), is a synthetic nonapeptide with diverse biological functions. In the present study, we investigated whether AF-1 has a protective effect against bleomycin-induced pulmonary fibrosis.MethodsC57BL/6 mice were injected with bleomycin intratracheally to create an animal model of bleomycin-induced pulmonary fibrosis. On Day 7 and Day 28, we examined the anti-inflammatory effect and antifibrotic effect, respectively, of AF-1 on the bleomycin-treated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 36 publications
(40 reference statements)
3
35
0
Order By: Relevance
“…In our study, we established the mouse pulmonary fibrosis model using a single intratracheal injection of bleomycin. Similar to previous observations, the lung tissue structural damage, inflammatory cells infiltration, and obvious edema were observed 7 days after bleomycin injection (Liu, Wan, Han, Li, Feng, Yue, Huang, Chen, Cheng, Li and Luo, 2013b). In addition, the Masson's trichrome stain results showed significant collagen deposition.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we established the mouse pulmonary fibrosis model using a single intratracheal injection of bleomycin. Similar to previous observations, the lung tissue structural damage, inflammatory cells infiltration, and obvious edema were observed 7 days after bleomycin injection (Liu, Wan, Han, Li, Feng, Yue, Huang, Chen, Cheng, Li and Luo, 2013b). In addition, the Masson's trichrome stain results showed significant collagen deposition.…”
Section: Discussionsupporting
confidence: 90%
“…The mice were randomly divided into three groups: (1) intratracheal saline (normal group); (2) intratracheal bleomycin plus vehicle (BLM group); (3) intratracheal BLM plus TPPU treatment (BLM +TPPU group). The mouse model of PF was established by an intratracheal injection of bleomycin (5 mg/kg, Nippon Kayaku, Japan) according to a previous published protocol (Liu, et al, 2013b). All surgeries were performed under anesthesia with an intraperitoneal injection of sodium pentobarbital (30 mg/kg).…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with this notion are the findings that PEX13 knockdown in fibroblast induce activation of TGF-β1 signaling, increased ROS, collagen and IL-6 production. Several studies have reported that ROS and release of proinflammatory cytokines are the main triggers of TGF-β1 signaling pathway, shown also during the peak of inflammation on day 7 using the bleomycin-induced lung fibrosis mouse model (1,25). Interestingly, in our bleomycin model, the strongest down-regulation of peroxisomes is also observed during day 7 (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…CC16 has anti-inflammatory activities in various models of pulmonary inflammatory diseases other than COPD such as allergen-induced airway inflammation 107;108 , bleomycin-induced pulmonary inflammation 109;110 , and airway respiratory syncytial viral infections and inflammation in mice 111 . It is noteworthy that macrophages are required for emphysema development in mice 112 , and CC16 reduced lung macrophage counts in CS-exposed mice 90 .…”
Section: Club Cell Protein-16 (Cc16)mentioning
confidence: 99%